2015
DOI: 10.1007/s10826-015-0280-x
|View full text |Cite
|
Sign up to set email alerts
|

Youth Emotional Reactivity, Interparental Conflict, Parent Hostility, and Worrying Among Children with Substance-Abusing Parents

Abstract: The present study examined whether emotional reactivity mediated the association between interparental violence, parental hostility, and children's worrying among 90 youth living with substance-abusing parents. Children completed measures of security and anxiety. Mothers and fathers' completed measures of violence perpetrated toward their partners and general hostility. Results of a Bayesian mediation model revealed indirect effects such that after controlling for other variables in the model, fathers' hostili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
(80 reference statements)
0
2
0
Order By: Relevance
“…Although studies of coercive cycles of parent-child interaction often focus on mothers, this pattern of findings extends to fathers as well (Denham et al 2000;Kelley et al 2016). For example, Wang and Kenny (2014) found that both mothers' and fathers' harsh verbal discipline of their young adolescents predicted escalation of teen's conduct and depressive symptoms over the next year.…”
Section: Candidate Mechanisms Of Change For Fathering In the Context Of Domestic Violencementioning
confidence: 99%
“…Although studies of coercive cycles of parent-child interaction often focus on mothers, this pattern of findings extends to fathers as well (Denham et al 2000;Kelley et al 2016). For example, Wang and Kenny (2014) found that both mothers' and fathers' harsh verbal discipline of their young adolescents predicted escalation of teen's conduct and depressive symptoms over the next year.…”
Section: Candidate Mechanisms Of Change For Fathering In the Context Of Domestic Violencementioning
confidence: 99%
“… 35 Consequently, if parents are overly sensitive to stressful events to the point of frequently expressing strong and persistent negative emotions, this will enhance their children’s concerns and fears, leading to intense negative emotion reactivity. 36 Besides, undergoing long-term exposure to their parents’ negative emotions and experiencing persistent high-intensity of that, children are vulnerable to various types of emotional problems. 37 Negative parenting styles are frequently practiced by parents with high emotion reactivity, which does not only diminish the quality of the parent-child relationship, but also threatens the establishment of children’s secure attachment with negative effects on their emotional development.…”
Section: Introductionmentioning
confidence: 99%